Supporting Chinese Undergraduate Students in Transition at U.S. Colleges and Universities - Montgomery, Kerrie A. (Journal of International Students, 2017)
The Chinese undergraduate student population currently represents 12.8% of all international students enrolled in the United States (Institute for International Education, 2015a). In an effort to understand the experiences of this population in their first year of college in the United States, a phenomenological study was conducted using a conceptual framework comprising Schlossberg’s Transition Model (Schlossberg, Waters, & Goodman, 1995) and the Culturally Engaging Campus Environments (CECE) Model (Museus, 2014). Three transition types were identified – academic, social/personal, and linguistic – and participants’ preparation, sources of institutional support, and coping strategies for moving through these transitions were examined. Recommendations for practice include: multi-faceted, mandatory orientation programs; ongoing workshops and resources beyond orientation; and improvements to housing and residential life opportunities and experiences.